First Approach to the Paleobiology of Extinct Prospaniomys (Rodentia, Hystricognathi, Octodontoidea) Through Head Muscle Reconstruction and the Study of Craniomandibular Shape Variation - Alvarez, Alicia (2015)
Prospaniomys is a basal octodontoid recorded in the early Miocene in Patagonia (Argentina; Colhuehuapian SALMA). Nearly complete cranial and mandibular remains known for this genus provide a unique opportunity to explore its paleobiology. For this, masticatory muscles were reconstructed and craniomandibular shape variation assessed. While such reconstruction indicates that most masticatory muscles would have presented moderate development, both the masseter lateralis and posterior muscles were poorly developed. In contrast, we found that the temporalis muscle was well developed, while conspicuous postorbital constriction, postorbital processes, and superior temporal lines revealed a substantial orbital portion of this muscle. According to geometric morphometric results, craniomandibular shape was interpreted as generalized. Features such as shortened palate, narrower bizygomatic width, orthodont incisors, enlarged incisive foramina, and a shallow jaw could be linked to epigean habits. The moderate development of auditory bullae in Prospaniomys suggests that it is unlikely that it may have lived in extreme arid environments. Additionally, based on its generalized dental morphology, an omnivorous or generalized herbivorous diet that may have included leaves, fruit, and potentially animal matter was inferred. By the early Miocene, Patagonia experienced the initial expansion stage of arid-adapted vegetation, with grasses present in low amounts and abundant forests. Generalized habits and soft and nonabrasive diet suggest that Prospaniomys was possibly associated with more closed environments. Morphology alone cannot be used as an environmental proxy, but it could undoubtedly contribute to the interpretations based on data provided by paleobotanical and geological frameworks in studies on the evolution of environments.